PENGARUH PENDEKATAN TaRL TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI POLA BILANGAN PESERTA DIDIK KELAS IV DI SDN MANGGONG - Tika Puspa Pandini; Ida Ermiana; Darmiany (STKIP Subang, 2025)
The low achievement in mathematics learning among fourth-grade students at SDN Manggong is caused by a significant gap in abilities between students due to the implementation of a uniform curriculum that has not been able to accommodate the diversity of actual individual abilities within the class. The purpose of this study is to analyze in more depth the effect of the TaRL approach on students' mathematics learning outcomes in number pattern material for fourth-grade students at SDN Manggong. This study is quantitative research with a Pre-Experimental Design using a One-Group Pretest–Posttest Design model. The study was conducted in the 2025/2026 academic year, precisely in December 2025, with 35 fourth-grade students at SDN Manggong as research subjects. The data collection techniques used were tests, observation, and interviews. The data were analyzed using descriptive analysis, data normality tests, N-Gain, and hypothesis testing using the paired sample T-test. Hypothesis testing in the study was conducted with the help of SPSS Version 29. The results of the study indicate that there is a significant effect of the TaRL approach on mathematics learning outcomes in the number pattern material for fourth-grade students at SDN Manggong. This is evident from the Sig. value of 0.001 < 0.05, so H0 is rejected and Ha is accepted. In addition, there was a significant increase in the average score from the pretest to the posttest by 26.97 points, from 61.91 to 88.89.